Upaya Meningkatkan Kreativitas Belajar Siswa Kelas XI TBSM di SMK Negeri 4 Kerinci pada Mata Pelajaran PPKN Melalui Penerapan Model Pembelajaran Inquiry - Febrianti, Dian; Salam, M.; Usmanto, Heri (Citizenship Education, Faculty of Education, Jambi University, 2022)
This iresearch was motivated by the low learning creativity of class XI TBSM students at SMK Negeri 4 Kerinci which was obtained by 16.90% who were creative in learning. Then the learning model used by the teacher when learning takes place does not have a tendency to improve students' creative thinking skills, students tend to be monotonous, students' knowledge is only limited to what is obtained from the teacher, students have difficulty in developing the knowledge gained from learning and students do not dare to express ideas, ideas or opinions. The purpose of this study is to find out that the inquiry learning model can ncrease the learning creativity of class XI TBSM students on Civics subjects at SMK Negeri 4 Kerinci. The design of this research is action research conducted by the teacher in the classroom. This research procedure is designed for 3 ciycles, where each cycle is carried out in 3 (three) face-to-face meetings. The action design in each cycle in this classroom action research is divided into 4 (four) stages, namel. Based on the results obtained during the implementation of classroom action research, it can be explained that the results of increasing student learning creativity in cycle I in this study showed the average percentage value of student learning creativity was 50%. Then classroom action research was carried out in cycle II where the average value of the percentage of student learning creativity became 64% which means it has increased but has not reached the KKM. Next, classroom action research is carried out in cycle III where the average value of the percentage of student learning creativity increases to 75% . This figure has shown that the average percentage value of student learning creativity has reached the KKM criteria of 75. Then it can be concluded that the application of the inquiry learning model at SMK Negeri 4 Kerinci can increase the learning creativity of class XI TBSM students in Civics.